Scientometric analysis in project virtual teams performance (LACCEI, 2024)
In a post-pandemic era, remote work has become part of the daily life of many people, and project management has not been immune to this phenomenon. For this reason, understanding how the study of performance in virtual project teams has evolved takes great importance in order to achieve the objectives of scope, time and cost in harmony with the personal and professional growth of the teams. The following paper shows a systematic literature review, to provide a status of the research dynamics on the performance of virtual project teams (VPT) based on the Scopus and Web of Science (WoS) databases in the last five years. The methodology implemented is the scientometric analysis of five steps (retrieval, migration, analysis, visualization, and interpretation). The study was based on 454 Q1 and Q2 papers, distributed in four clusters largely dominated by USA and Europe. The analysis allows us to identify key variables for high performance in VPTs, such as communication, leadership, and trust, as well as other relevant variables associated with technology and management. Additionally, it was possible to identify a few research developments in Spanish-speaking countries.